Echolocation inter-click interval variation among specific behaviours in free-ranging bottlenose dolphins from the coast of Uruguay - Tellechea, Javier (J. Cetacean Res. Manage., 2020)
To assess whether behaviour can be inferred from echolocation trains (inter-click intervals) this study examines acoustic recordings of free-ranging bottlenose dolphins using Passive Acoustic Monitoring (PAM). Inter-click intervals from 17 groups of free-ranging bottlenose dolphins were monitored over a 36 day period in an area within the Cerro Verde (Marine Protected Area), Uruguay. Simultaneous visual observations were made from shore nearby. Results show that inter-click intervals in the echolocation trains had significant differences for three specific behaviours: feeding, socialising and travelling. The natural environment was quiet, with no disturbances in the immediate vicinity from boats, drones or other man-made noises.